Introductory investigations of some nematodes associated with apple trees in the Grabouw area - Hugo, H. J.(Hans Jurgens) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1984.